Violencia, valor y resistencia en la migración centroamericana en tránsito. Una propuesta para su análisis - Salazar Araya, Sergio (2023)
Based on ethnographic work in Central America and Mexico, the article outlines an analysis strategy for Central Americanmigration in transit from an anthropological perspective. The migratory processes are produced from a specific transnational social distribution of labor that is spatialized in assemblages from which the necessary tasks to produce forms of mobility are performed. This distribution includes, on the one hand, the concrete transit actions structured by forms of violence that are linked to the extraction of forms of value from the mobility of a dispossessed, exploited and precarious population, on theother, the processes of its political and subjective constitution.